Pengaruh Pemberian Ekstrak Etanol Daun Mangrove Api-Api Putih (Avicennia Alba) Terhadap Kesembuhan Ulkus Traumatikus - Devy Tri Wulandari P; Isidora Karsini S; Dian Mulawarmanti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Ulcers are common and cause pain, difficulty in speaking, eating and swallowing. Avicennia alba role in the process of wound healing and has been shown to accelerate the healing process of gastric ulcer. It contains flavonoid, saponin, NSLcomponents, minerals and vitamin C, which plays a role in wound healing. Purposes: To prove the effect of ethanol extract of Avicennia alba consentration 10%, 20%, 40% against traumatic ulcer. Materials and Methods: The subjects of this research were 30 wistar rats that were randomized into 5 different groups; K0, K1, P1, P2 and P3. (K0) control, (K1) were given hyaluronic acid, (P1) were given extract of Avicennia alba 10%, (P2) were given extract of Avicennia alba 20%, and (P3) were given extract of Avicennia alba 40%. The subject was wounded using amalgam stopper that has been heated before. Subject was given topical application once daily. The ulcer’s diameter was measured at the second day until the day cured using digital caliper. Data were analyzed using One way ANOVA test. Result: The result showed signification of p<0,05, showed that there were difference diameters betweentwo groups. The average diameter differences of traumatic ulcer among rat are: 0,75 mm (K0), 1,51 mm (K1), 1,01 mm (P1), 2,02 mm (P2), and 1,70 mm (P3). The results showed statistically significant value of p>0.05 which there was no difference in effectivenessAvicennia alba extract in the K1 group. Conclusions: Ethanol extract of Avicennia alba 10%, 20%, and 40% have effect in the healing of traumatic ulcer. The effectiveness of those were the same as giving a 0.2% hyaluronic acid. The concentration 20% of Avicennia alba was effective to the healing of traumatic ulcer